Isolasi dan Penentuan Kadar Minyak Nilam (Pogostemon cablin Benth) Asal Peunaron Kabupaten Aceh Timur Menggunakan GC-MS - Daniati, Ela; Mastura, Mastura; Hasby, Hasby (Universitas Samudra, 2021)
This study aims to determine the result of isolation of patchouli oil from Peunaron East Aceh and determine the quality of patchouli oil and to determine the levels contained in patchouli oil. Analysis of the results of the research data is described using quantitative and descriptive analysis. Based on research that has been done that the results of isolation of patchouli oil from Peunaron , East Aceh Regency, yields a value of 2,04%. Patchouli oil quality obtained shows yellow results with a specific gravity value of 0,950 that meets SNI standards. The determine of the refractive index produces a value of 1,50039 with results that do not meet SNI standards and the resulting patchouli oil content is 33 chemical compound components with the main component of patchouli alcohol content of 3,65%. It can be concluded that patchouli oil from Peunaron, East Aceh Regency still does not meet SNI standards.